Key factors influencing P2P lending adoption in Vietnam - Hieu, Le Trung; Huong, Tram Thi Xuan; Ha, Nguyen Hong (The Economics and Finance Letters, 2026)
This research examines the salient drivers of the adoption of peer-to-peer (P2P) lending in Vietnam, a fast-growing country with expanding digitalized finance activities. This research is grounded in theories of trust, perceived risks, regulation, economic behaviors, and technological innovation. From these theoretical foundations, five key drivers are derived: trust, perceived risk, regulatory framework, economic status, and usefulness of technology. A quantitative method was used, based on 285 respondents from Hanoi and Ho Chi Minh City, with the analysis employing multiple linear regression to investigate the effect of independent variables on the adoption of P2P lending. The findings demonstrate that all five drivers have a significant effect on the usage of P2P lending, with perceived risk and trust having the greatest impact. The research calls for the reinforcement of user trust by enhancing transparency of the platforms and secure operation, reducing perceived risks, and issuing clearer regulation policies. Economic stability and user-friendly technology are key facilitators for widespread adoption. The research contributes to the expanding FinTech literature in emerging economies and provides actionable recommendations for policymakers, platform developers, and financial institutions to support the sustainable growth of P2P lending within Vietnam.